Simulation and Simulacra in Aldous Huxley’s Brave New World: A Baudrillardian Appraisal - Md. Mozaffor Hossain (J-Lalite: Journal of English Studies, 2022)
Aldous Huxley’s Brave New World portrays a post-human totalitarian society namely “World State” which does not let humans be conceived in and born naturally from mothers’ wombs, rather it regards them as any creature which can be hatched, conditioned, fertilized, incubated and Bokanovskified to be manufactured in thousands. The system of power has thrown normality into exile while celebrating the procession of replicating humans in abnormal proliferation. I find this technological multiplication of humans identical to the march of simulacrum of any object or sign of today’s world, which Jean Baudrillard (1929-2007) elucidates in his Simulacra and Simulation (1981). This study intends to achieve a critical appraisal of the novel through Baudrillard’s illumination of simulation and simulacra